A hegemonic nuclear order: Understanding the Ban Treaty and the power politics of nuclear weapons. Issue 4 (2nd October 2019) - Ritchie, Nick
ABSTRACT: The notion of a "global nuclear order" has entered the lexicon of nuclear politics. The 2017 Treaty on the Prohibition of Nuclear Weapons has prompted further questions about how we understand it. Yet missing from analysis of nuclear order and the "Ban Treaty" is a critical analysis of the power relations that constitute that order. This article develops a critical account of global nuclear order by applying Robert Cox's concept of hegemony and power to the global politics of nuclear weapons, drawing on the politics of the Ban Treaty. It theorizes a "nuclear control order" as a hegemonic structure of power, one that has been made much more explicit through the negotiation of the Ban Treaty. This fills a void by taking hegemony and power seriously in theorizing nuclear order, as well as explaining both the meaning of the Ban Treaty and its limits.